A Techno-Economic Feasibility Study of Electricity and Hydrogen Production in Hybrid Solar-Wind Energy Park. The Case Study of Tunisian Sahel - Slah Farhani (21393992) (2024)
This paper provides a comprehensive analysis of the potential for integrating renewable energy sources to meet the growing electricity and hydrogen demand in the Tunisian Sahel region, focusing particularly on solar and wind energies. The feasibility of installing a hybrid solar-wind energy system capable of producing both electricity and hydrogen is evaluated. With the help of the available solar and wind resources combined, the system not only generates electric power, but also produces hydrogen gas through electrolyzation, hence offering a multipurpose solution in terms of storage and supply. This flexibility is crucial due to the variability of renewable resources, which change daily and seasonally. The paper outlines the optimization process for designing the hybrid system deploying HOMER Pro software, according to local climatic conditions and demand profiles. The economic analysis reveals that the system can produce an average of 101.8 kg of hydrogen daily with a total photovoltaic capacity of 3,000 kWp, resulting in a project net cost estimation of approximately 5,494,912 euros. This analysis provides valuable insights for stakeholders considering similar projects, including the costs associated with photovoltaic systems, electrolyzers, and hydrogen storage solutions. Other Information Published in: Engineering, Technology & Applied Science Research License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.48084/etasr.7394